2018
DOI: 10.1111/jir.12581
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, bone mineral density and risk of fracture in people with intellectual disabilities

Abstract: Background People with intellectual disabilities (IDs) have very high rates of osteoporosis and fractures, to which their widespread vitamin D deficiency and other factors could contribute. We aimed to assess in people with IDs previously treated for vitamin D deficiency (1) long-term adherence to vitamin D supplementation and (2) bone mineral density (BMD), as an indicator for risk of fractures, according to vitamin D supplementation and other factors. Method We recorded height, weight, medical, pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…This may indicate a need for a higher serum level of 25-hydroxy vitamin D, more weight-bearing physical activity, or both. Additionally, since we did not have a control group treated with vitamin D alone, we cannot rule out the possibility that the improved BMD observed in our study was more the result of treatment with vitamin D rather than bisphosphonate, since recent reports have demonstrated suppressive effects of vitamin D on PTH and CTX in ambulatory males with intellectual disability who were never treated with bisphosphonates (Frighi et al, 2019;May & Winters, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…This may indicate a need for a higher serum level of 25-hydroxy vitamin D, more weight-bearing physical activity, or both. Additionally, since we did not have a control group treated with vitamin D alone, we cannot rule out the possibility that the improved BMD observed in our study was more the result of treatment with vitamin D rather than bisphosphonate, since recent reports have demonstrated suppressive effects of vitamin D on PTH and CTX in ambulatory males with intellectual disability who were never treated with bisphosphonates (Frighi et al, 2019;May & Winters, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…In terms of current practice, there is evidence to suggest that long‐term vitamin D supplementation in the learning disability population is beneficial to bone health. Frighi et al () demonstrated an improvement in bone mineral density for people with learning disability previously diagnosed with vitamin D deficiency. Current guidance from the Scientific Advisory Committee on Nutrition () regarding vitamin D supplementation for the UK population recommended a Reference Nutrient Intake (RNI) for vitamin D of 10 μg daily (400 IU daily) for all aged 4 and above.…”
Section: Discussionmentioning
confidence: 99%
“…People with learning disability (LD) experience a higher rate of injuries, falls and accidents (Finlayson, Morrison, Jackson, Mantry, & Cooper, ). The rate of osteoporosis and fractures is up to three times that of the general population (Frighi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rates of chronic disease are overall higher for individuals with intellectual disability in comparison to the general population [4,8]. One condition that is highly prevalent within this population is osteoporosis [9][10][11]. Research has sought to explore and understand the prevalence for poor bone health among people with an intellectual disability and prevalence rates of over 70% have been identified [12].…”
Section: Introductionmentioning
confidence: 99%